2020
DOI: 10.1021/acs.macromol.9b02611
|View full text |Cite
|
Sign up to set email alerts
|

Shear Flow-Induced Crystallization of Poly(ether ether ketone)

Abstract: When a semicrystalline polymer melt is subjected to sufficient flow before crystallization, the nucleation rate is accelerated. In this study, the degree of acceleration is investigated with a commercial poly(ether ether ketone), using a rotational rheometer. With a constant shearing time (t s = 1 s), the nucleation rate increases with the shear rate (10 s −1 < γ̇< 200 s −1 ). At a constant shear rate (γ̇= 20 s −1 ), the nucleation rate increases with the shearing time (1 s < t s < 15 s). For a constant strain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
43
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(44 citation statements)
references
References 45 publications
1
43
0
Order By: Relevance
“…This result implies that only ∼1% of the mechanical energy input reduces the entropy-relevant free energy due to the dominance of friction and relaxation effects. 27 In P3HT toluene solution, the high concentration solution has high viscosity, which may dissipate more mechanical energy under shear, namely, E is low in high concentration solution. To reduce the entropy to accelerate nucleation and crystallization, a higher W was needed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This result implies that only ∼1% of the mechanical energy input reduces the entropy-relevant free energy due to the dominance of friction and relaxation effects. 27 In P3HT toluene solution, the high concentration solution has high viscosity, which may dissipate more mechanical energy under shear, namely, E is low in high concentration solution. To reduce the entropy to accelerate nucleation and crystallization, a higher W was needed.…”
Section: Resultsmentioning
confidence: 99%
“…Such enhanced crystallization kinetics are mainly attributed to the signicantly increased nucleus density and growth rate, namely, the shear ow would eventually lead to an increased nucleation rate once the shear rate exceeds a critical value. 21,27 Under shear, polymer chains aligned along the shear direction, reducing the entropy due to fewer possible chain congurations. From a thermodynamic point of view, Flory proposed that the reduction in entropy lowers the nucleation energy barrier ðDG * n Þ, resulting in nucleation acceleration.…”
Section: Effect Of the Shear Temperature On The Solution Crystallization Kineticsmentioning
confidence: 99%
“…Figure 1 depicts the time–temperature protocol to monitor non‐isothermal crystallization kinetics of PEEK at the cooling rates of 10, 30, 50, 70, and 90 K/min. Our previous publication [ 24, 25 ] reported that shear history can accelerate the crystallization kinetics of PEEK. Thus, non‐isothermal crystallization kinetics was monitored after erasing the shear history at 400°C above the equilibrium melting temperature of Tm°=380°normalC, [ 10 ] for 5 min.…”
Section: Methodsmentioning
confidence: 99%
“…(II) As the shear rate reaches 1 s –1 , an abrupt increase in birefringence was clearly observed (see the birefringence image at γ̇ = 1 s –1 and Figure S2), implying a significant structural change attributed to the I–N transition. ,, The border between Regimes I and II has a relaxation time corresponding to 1/γ̇ = 1 s. This might represent the Rouse time τ R of the longest chains, where such long chains get significantly stretched along the flow direction. , As γ̇ increases, the failure of the Cox–Merz empirical rule manifests. On a similar PEEK melt, sheared at 350 °C, Nazari et al assigned the failure of the Cox–Merz rule to the onset of flow-induced crystallization (FIC) precursors, with accelerated crystallization kinetics.…”
mentioning
confidence: 96%
“…12,28,40 The border between Regimes I and II has a relaxation time corresponding to 1/γ̇= 1 s. This might represent the Rouse time τ R of the longest chains, where such long chains get significantly stretched along the flow direction. 36,41 As γ̇increases, the failure of the Cox−Merz empirical rule 42 manifests. On a similar PEEK melt, sheared at 350 °C, Nazari et al 36 assigned the failure of the Cox−Merz rule to the onset of flow-induced crystallization (FIC) precursors, with accelerated crystallization kinetics.…”
mentioning
confidence: 99%